MANAJEMEN PEMBIAYAAN UNTUK MENINGKATKAN PENGELOLAAN PENDIDIKAN - Oviria; Zamirna; Wahyuningsih (UNISAN JURNAL, 2022)
This journal describes financial management in improving education management in schools and madrasahs. The results found include: first, the feasibility of infrastructure, facilities, human resources, as well as facilities and infrastructure because the availability of qualified financing at SMPN 10 Bandar Lampung is directly proportional to the quality of education. Regular students achieve academic and non-academic achievements. Many of the graduates of SMP Negeri 10 Bandar Lampung are also scattered in high schools which are in the favorite category; Secondly, high motivation from various elements in MTs Mathla’ul Anwar Labuhan Ratu Bandar Lampung especially school principals and educators also has a major effect on the quality of education. Given, a number of madrasah graduates are also able to compete to enter secondary schools which are classified as favorites.